2021
DOI: 10.3389/fimmu.2021.661204
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Modulation of Cancer and Immune Pathways in Hepatitis B Virus-Associated Hepatocellular Carcinoma: The Influence of HBx and miRNA Dysregulation

Abstract: Hepatitis B virus (HBV)-associated hepatocellular carcinoma (HBV-HCC) pathogenesis is fueled by persistent HBV infection that stealthily maintains a delicate balance between viral replication and evasion of the host immune system. HBV is remarkably adept at using a combination of both its own, as well as host machinery to ensure its own replication and survival. A key tool in its arsenal, is the HBx protein which can manipulate the epigenetic landscape to decrease its own viral load and enhance persistence, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 238 publications
(204 reference statements)
0
33
0
Order By: Relevance
“…Attenuation of the antiviral immune response can also be accomplished by HBx-mediated epigenetic modulation and miRNA dysregulation [ 133 ]. HBx-dysregulated tumour suppressor miR-101 reduces LPS-stimulated macrophage expression, capable of inducing HCC, due to its inability to modulate DUSP1 phosphatase enzyme, which leads to impaired ERK1/2/p38/JNK elevation of pro-inflammatory cytokines such as TGF-β [ 134 ].…”
Section: Evading Immune Destructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation of the antiviral immune response can also be accomplished by HBx-mediated epigenetic modulation and miRNA dysregulation [ 133 ]. HBx-dysregulated tumour suppressor miR-101 reduces LPS-stimulated macrophage expression, capable of inducing HCC, due to its inability to modulate DUSP1 phosphatase enzyme, which leads to impaired ERK1/2/p38/JNK elevation of pro-inflammatory cytokines such as TGF-β [ 134 ].…”
Section: Evading Immune Destructionmentioning
confidence: 99%
“…HBx-dysregulated tumour suppressor miR-101 reduces LPS-stimulated macrophage expression, capable of inducing HCC, due to its inability to modulate DUSP1 phosphatase enzyme, which leads to impaired ERK1/2/p38/JNK elevation of pro-inflammatory cytokines such as TGF-β [ 134 ]. To gain a more comprehensive insight into HBx influence on a plethora of miRNA dysregulation pathways and their associated immune response, refer to Sartorius et al [ 133 ].…”
Section: Evading Immune Destructionmentioning
confidence: 99%
“…Several studies showed a role for HBx in up- and downregulating the expression of cellular microRNAs, including miR-10, miR-132, miR-143, and miR-193b. This has been the topic of excellent reviews [ 190 , 255 , 257 , 263 , 291 , 292 ]. HBx modulates microRNA expression by inducing epigenetic changes in microRNA-encoding genes or modulating expression of genes whose products are involved in microRNA biogenesis.…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…Moreover, HBx can repress Drosha expression leading to dysregulation of microRNA biogenesis [ 298 ]. MicroRNAs modulated by HBx were demonstrated to target genes that encode proteins involved in cell cycle progression, cell survival, immune evasion, invasiveness and migration, and angiogenesis [ 292 ]. Thus, dysregulation of microRNA expression is a pivotal mechanism by which HBV promotes hepatocellular carcinogenesis.…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…An early study showed that altered host gene expression by HBx caused the occurrence of HCC in transgenic mice [ 13 ]. The HBx protein regulates its target genes through epigenetic modification in the pathogenesis of HBV–HCC [ 14 ]. In a previous study, we confirmed that activation of key oncogenes by epigenetic modification is a key factor leading to the occurrence and development of HBV-related HCC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%